Automated reasoning in a collaborative problem solving process : A first approach - Casalini, María Clara (2008)
Collaborative systems are becoming a widely used tool particularly among professional communities and research groups. They provide a suitable context for distributed people working on the same subject to concentrate their work in a shared place to which everyone has access and can keep updated. The Semantic Web, intended to provide well defined semantics and cooperation between machines and people offers a range of technologies that underpin the development of intelligent collaborative systems. Defeasible reasoning has been shown to appropriately model common-sense reasoning. This work presents a first approach to incorporating defeasible reasoning with a software agent that collaborates with humans in a collaborative problem solving process. The process relies in a shared knowledge repository which is also modeled to incorporate defeasible knowledge